Study of Anti-Ovarian Antibody, Anti-FSH and Anti-LH Antibodies Along with Their Receptors in Polycystic Ovarian Syndrome - Rabab Mohammed Abood; Huda Dhaher Hathal (Indian Journal of Forensic Medicine & Toxicology, 2021)
A case control study was conducted to compare sixty females (polycystic ovarian syndrome patients ), thirtywith high LH & FSH hormone level “Group 1 “ G1”, thirty with low LH & FSH hormone level “ Group2 “ G2 “ and thirty healthy control groups. The average age is between (15 – 45 years). The followingparameters were estimated: Luteinizing Hormone (LH), Luteinizing Hormone-Receptor (LH-R), Folliclestimulating hormone (FSH) , Follicle-stimulating hormone-Receptor (FSH-R), anti-LH ,anti-FSH , antiovarian antibody (by ELISA Technique ).Rresults showed that the average age of the patients within the first group1( G1) was 28 year, whilethe average age of the patients in the second group2( G2) was 36 years, also the results showed a highcorrelation between group1 ( G1 ) with (Anti FSH antibodies ) (93%), compared with group2 (G2) that(Anti FSH antibodies ) where it was 0% , as well a high correlation 100% between group1 (G1) with (AntiLH antibodies),compared with group2 (G2) where it was 3% . And anti-ovarian antibodies ,compared withgroup 2 .